The Question of Accountability: New Forms or a Democratic Deficit - Peter, Idoko (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
This research examined the question of accountability; new forms or a democratic deficit. The study examined specially examines the relationship between transparency and accountability, relationship between technocratic decision making and accountability and finally the relationship between proper coordination and accountability. The study is an exploratory study that used mainly secondary sources of information obtained from journals, text books and from the internet. The findings from the review shows that public accountability is important because it provides a democratic means to monitor and control government conduct, prevent the development of concentrations of power, and enhance the learning capacity and effectiveness of public administration. This is because rulers can be investigated and held to account for actions that transgress the law or result in personal enrichment or violate common mores. These tenets are lacking in our public institutions and in broader perspective the government. The study concludes that large changes in politics, especially for the citizens of the European Union, with the latest enlargement in which brought the union to 27 member states and a half a billion people has been recorded, raising questions on issues such as democracy and the peoples options of accountability. It was recommended among others that it will be fair for all the operators to play the game of leadership according to the established rules and regulations to promote transparency. Also, the experts are to be given free hand to exercise their expertise to usher in accountability for the growth of the system. It was also recommended that it is advisable for all the operators to exhibit probity to eliminate fraudulent behavior.